Placental MRI Predicts Fetal Oxygenation and Growth Rates in Sheep and Human Pregnancy. Issue 30 (28th August 2022) - Flouri, Dimitra; Darby, Jack R. T.; Holman, Stacey L.; Cho, Steven K. S.; Dimasi, Catherine G.; Perumal, Sunthara R.; Ourselin, Sebastien; Aughwane, Rosalind; Mufti, Nada; Macgowan, Christopher K.; Seed, Mike; David, Anna L.; et al.
Abstract: Magnetic resonance imaging (MRI) assessment of fetal blood oxygen saturation (SO2 ) can transform the clinical management of high‐risk pregnancies affected by fetal growth restriction (FGR). Here, a novel MRI method assesses the feasibility of identifying normally grown and FGR fetuses in sheep and is then applied to humans. MRI scans are performed in pregnant ewes at 110 and 140 days (term = 150d) gestation and in pregnant women at 28 +3 ± 2 +5 weeks to measure feto‐placental SO2 . Birth weight is collected and, in sheep, fetal blood SO2 is measured with a blood gas analyzer (BGA). Fetal arterial SO2 measured by BGA predicts fetal birth weight in sheep and distinguishes between fetuses that are normally grown, small for gestational age, and FGR. MRI feto‐placental SO2 in late gestation is related to fetal blood SO2 measured by BGA and body weight. In sheep, MRI feto‐placental SO2 in mid‐gestation is related to fetal SO2 later in gestation. MRI feto‐placental SO2 distinguishes between normally grown and FGR fetuses, as well as distinguishing FGR fetuses with and without normal Doppler in humans. Thus, a multi‐compartment placental MRI model detects low placental SO2 and distinguishes between small hypoxemic fetuses and normally grown fetuses. Abstract : The authors use a sheep model of human pregnancy to validate magnetic resonance imaging (MRI) fetal oxygenation measurements with invasive blood gas‐samples. They present evidence that this method is predictive of fetal growth rate in sheep and human pregnancies. These findings may lead to development of novel MRI‐based diagnostic tool for tracking fetal oxygenation in pregnancies complicated by placental insufficiency.